2020
DOI: 10.1371/journal.pone.0233961
|View full text |Cite
|
Sign up to set email alerts
|

Integration of phage and yeast display platforms: A reliable and cost effective approach for binning of peptides as displayed on-phage

Abstract: Hundreds of target specific peptides are routinely discovered by peptide display platforms. However, due to the high cost of peptide synthesis only a limited number of peptides are chemically made for further analysis. Here we describe an accurate and cost effective method to bin peptides on-phage based on binding region(s), without any requirement for peptide or protein synthesis. This approach, which integrates phage and yeast display platforms, requires display of target and its alanine variants on yeast. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The results of these competition experiments confirmed that the IL-23:IL12Rβ1 complex had a high affinity for the untagged IL-23 cytokine, K D = 27.2 ± 12.0 pM, which was similar to that measured for IL23-TMR. In the context of a growing list of reported IL23R antagonists ( Cheng et al., 2019 ; Kong et al., 2020 ; Kuchař et al., 2014 ; Pandya et al., 2020 ; Quiniou et al., 2014 ), this assay should be a useful tool for future screening efforts to identify and develop IL-23 receptor inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these competition experiments confirmed that the IL-23:IL12Rβ1 complex had a high affinity for the untagged IL-23 cytokine, K D = 27.2 ± 12.0 pM, which was similar to that measured for IL23-TMR. In the context of a growing list of reported IL23R antagonists ( Cheng et al., 2019 ; Kong et al., 2020 ; Kuchař et al., 2014 ; Pandya et al., 2020 ; Quiniou et al., 2014 ), this assay should be a useful tool for future screening efforts to identify and develop IL-23 receptor inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast surface display, alone or in combination with phage display, starts to be an approach for the quick identification of protein binders, with only a few examples to express cyclic peptide derivatives nowadays. Thus, genetically encoded libraries generated by using yeast surface display serve to identify cyclic peptides that bind to lysozyme, interleukin-17 (IL-17) and IL-23 [ 59 , 60 ], and help to envisage this technique as a future strategy toward peptide drug leads and inhibitors of relevant PPIs. Another attractive, completely in vitro method for library production is the mRNA display, which allows the insertion of non-natural amino acid residues and peptide cyclization [ 61 , 62 ], though the application to find PPI binders need to be explored yet.…”
Section: Main Methodologies To Cyclic and Macrocyclic Peptidesmentioning
confidence: 99%
“…At present, many targets that cannot be targeted by small molecules are degraded by peptide PROTACs ( Table 2 ). Another way to develop targeting peptides with high affinity for POI is to use phage display and yeast display technologies 49 , 50 ,which can find hundreds of target-specific peptides 51 , 52 . More importantly, these technologies do not rely on protein crystal complexes, and can obtain d -configuration peptide targeting warheads, which can avoid the easily degradable characteristics of peptide ligands in the body 53 .…”
Section: Peptide Protacsmentioning
confidence: 99%